Dampak Literasi Keuangan Terhadap Kinerja Umkm dengan Inovasi Sebagai Variabel Moderasi: Perspektif Keberlanjutan Umkm - Pulkeria Destrin (Jurnal Literasi Akuntansi, 2024)
Purpose: This study aims to prove the positive effect of financial literacy and innovation on MSME performance, as well as moderate the role of innovation in the relationship between financial literacy and MSME performance Method: This research is quantitative research and the verification analysis approach is the method applied, the primary data is obtained through distributing questionnaires to MSME actors. The sampling technique in this study used purposive sampling, the criteria used were Micro, Small and Medium Enterprises (MSMEs) in Yogyakarta City. Finding: The results of the analysis obtained that partially, financial literacy and innovation have a positive and significant effect on MSME performance in the perspective of MSME sustainability. while innovation is unable to moderate financial literacy on MSME performance. Novelty: In previous research, innovation is used as an independent variable while in the current study innovation is used as a moderating variable.